Covid-19 and Efficiency in Zakat Institutions: Evidence from Indonesia - Muhammad Syamsul Bahri; Evania Herindar; Aam Slamet Rusydiana (AKSES: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to investigate the efficiency of Zakat institutions in Indonesia. To examine the efficiency of Zakat institutions, we employed the Data Envelopment Analysis method. The objects in this study are 17 Zakat institutions in Indonesia, classified into two: public Zakat institutions and private Zakat institutions. The data in this study comes from the annual reports of 17 Zakat institutions in Indonesia during the 2014-2020 period. The input variables in this study include salaries expense, operational expense, and total assets. The output variables in this study include Zakat collected and Zakat distributed. The results of this study indicate that during 2014-2020, the efficiency of Zakat institutions has a fluctuating trend. In 2014-2016, public Zakat institutions experienced a successive increase in efficiency before experiencing a decline in the 2017-2018 period. Efficiency of public Zakat institutions increased again from 2018 to 2019 but stagnated in the 2019-2020 period. In contrast, efficiency of private Zakat institutions decreased successively during the 2014-2016 period and experienced a slight increase in 2017 before declining again in 2018. However, private Zakat institutions experienced a significant increase in the 2018-2020 period. This study also reveals that private Zakat institutions are generally more efficient in managing inputs and maximizing desired outputs than public Zakat institutions. Moreover, to portray the efficiency level of Zakat institutions during Covid-19, we analyze the efficiency level of Zakat institutions in Indonesia in the 2019-2020 period as a whole. The results of this study found that overall, Zakat institutions in Indonesia experienced a significant trend of increasing efficiency value.